ANALYSIS OF MAUDHUIY'S TAFSIR METHOD: A THEMATIC APPROACH IN INTERPRETING THE QUR'AN - Lubis, Nanang Ardiansyah; Milhan, Milhan (SYAHADAT: Journal of Islamic Studies, 2024)
Tafsir Maudhuiy method is a systematic approach in interpreting the Quran based on certain themes, which provides a more holistic and applicable understanding of Islamic teachings. This study describes the history, requirements, steps, analysis, and implications of this method, both in general and in Indonesia. The history of the development of Tafsir Maudhuiy method shows the contribution of figures such as Muhammad Abduh, Rashid Rida, and Quraish Shihab in its development and application. The requirements and steps include mastery of Arabic language, Quranic sciences, and high analytical skills to identify the main themes of the Quran. An analysis of the method highlights its superiority in addressing contemporary issues in Islamic society. The implications of applying this method include the possibility of developing more in-depth and applicable thematic studies, as well as practical guidance for Muslims in dealing with modern challenges. Future projections show a bright prospect with an increased understanding and application of the Tafsir Maudhuiy method in various contexts, although it requires in-depth knowledge and objectivity in the interpretation of the Quran